C/EBPβ increases tumor aggressiveness by enhancing KIFC1 expression in androgen receptor negative triple negative breast cancer - Shriya Joshi; Chakravarthy Garlapati; Thi Nguyen; Shaligram Sharma; Darshan Shimoga Chandrashekar; Shristi Bhattarai; Sooryanarayana Varambally; Uma Krishnamurti; Xiaoxian Li; Ritu Aneja (Cell Communication and Signaling)
Abstract Quadruple-negative breast cancers (also known as AR-triple negative (TN) BC) lack the expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and androgen receptor (AR). AR-TNBC exhibits aggressive characteristics and a poor prognosis. Because of the lack of expression of therapeutic targets, limited therapeutic options exist for patients with AR-TNBC. Hence, new therapeutic targets and risk-predictive biomarkers are required for patients with AR-TNBC. In this study, we investigated the role of kinesin-like protein 1 (KIFC1) in AR-TNBC. We found that C/EBPβ binds to the KIFC1 promoter and induces its expression in the AR-TNBC cells. Notably, AR status was negatively correlated with KIFC1 levels. We also found that AR transcriptionally repressed the transcription factor C/EBPβ, which regulates the expression of KIFC1. The lack of AR expression in AR-TNBC led to C/EBPβ upregulation, thereby enhancing KIFC1 expression. Moreover, upregulation of KIFC1 in AR-TNBC increased cancer cell proliferation and promoted epithelial-mesenchymal transition (EMT), contributing to the aggressive characteristics of AR-TNBC. Inhibiting KIFC1 using the small molecule inhibitor CW069 significantly reduced tumor volume in mice bearing AR-TNBC xenografts, but not in those with triple-negative breast tumors. These data suggest that upregulation of C/EBPβ and KIFC1 contributes to the aggressive characteristics and poor prognosis of AR-TNBC, providing strong evidence that targeting KIFC1 using kinesin inhibitors could be a viable therapeutic approach for patients with AR-TNBC. Graphical Abstract